PEMBANGKIT LISTRIK ENERGI MATAHARI SEBAGAI PENGGERAK POMPA AIR DENGAN MENGGUNAKAN SOLAR CELL - -, Subandi; Hani, Slamet (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2015)
This paper discusses the application of solar cells as an electric power source and the electricity generated is used to a drive water pump. The working principle of solar power plants is the conversion of energy contained in to electricity. When these photons strike the surface of the solar cell electrons will be excited and generate electric voltage. Electricity generated from the solar cell is direct current (DC) to charge a battery, which in turn is converted into alternating current (AC) using an inverter. The testing stage carried out in the field is to find the to main parameters whichare the voltage and amperage. Battery is charged by the solar cell to accumulate the solar energy into electrical energy. The produced solar cell voltage ranges from 14.8 to 17.5 volts DC. The Solar cells used are of panel type polycrystalline (poly-crystalline) with a power of 50 wp. Current and voltage of the solar cell source varies depending on the incident sunlight power the cell voltage is Â± 17V, but charging the battery the average voltage is 13,5V which is secured by the solar charger controller. Voltage and current will begin to rise in the morning at 07.00 am, then reach the maximum level during the day at 10:00 a.m to 13:00 p.m, and begin to fall in the afternoon.